Breast Cancer in the Modern Era: Molecular Strategies for Tumor Targeting and Diagnosis - Baig, Muhammad Haris (African Journal of Medicine, Surgery and Public Health Research, 2025)
Breast cancer is a multifactorial and heterogeneous malignancy arising from the uncontrolled proliferation of breast tissue cells, primarily affecting women but also occurring in men. Among its various subtypes, invasive ductal carcinoma (IDC) accounts for 70% to 80% of cases, making it the most prevalent form. As one of the leading causes of cancer-related mortality among women globally, breast cancer remains a major public health concern, driving continuous research into its etiology, detection, and treatment. The disease is influenced by an interplay of genetic, hormonal, and environmental risk factors. While non-modifiable determinants such as age and sex are critical, modifiable lifestyle factors, such as physical activity, dietary habits, and alcohol consumption also contribute significantly to disease risk. Advances in screening technologies, including mammography and magnetic resonance imaging (MRI), have facilitated earlier detection, improving treatment outcomes. However, disparities in access to diagnostic and therapeutic resources persist, particularly in low-resource and marginalized populations, reinforcing existing health inequities. The treatment landscape has evolved markedly with the advent of personalized medicine and immunotherapeutic approaches, offering targeted interventions based on tumor biology. Nevertheless, ongoing challenges include treatment resistance, overdiagnosis, and the ethical dilemmas surrounding management of low-risk lesions. Furthermore, debates continue regarding optimal screening strategies, the role of genetic testing, and the balance between therapeutic benefit and potential harm. These complexities underscore the need for integrative, equity-focused approaches to breast cancer prevention, diagnosis, and care.